Whether the Current Regulatory Framework is Adequate to Address the Challenges in Claims Procedure in Property Insurance in Uganda - Christmas Agaba (Uganda Christian University, 2024)
With the constant growth of the economy, issues of insurance (claims ettlements) are a growing concern and as such the law governing property insurance is one that needs to be considered. This research sought to evaluate the adequacy of the Uganda Regulatory framework in addressing the challenges in the claims procedure regarding property insurance. In that regard, the study took a comparative analysis of different laws in other jurisdictions to identify the loopholes within the claims settlements operations under property insurance law in Uganda and make recommendations and proposals for Reforms. The research brought out a plethora of challenges such as fraud, unfair settlement practices, inadequate settlements, complex documentation, delay in claims settlements, disputes over coverage and knowledge gaps among others. The research paper recommends that the Regulatory bodies and Insurance companies need to increase claims settlement limits for branches, provide platforms to explain the technical language used in the policy to customers that may not understand the language. It proposes for the Amendment of the property insurance Laws to include time-frames within which claims must be settled. It further proposes for the provision of penalties in respect to the violation of the same.